Intrahepatic upregulation of RhoA and Rho-kinase signalling contributes to increased hepatic vascular resistance in rats with secondary biliary cirrhosis. Issue 9 (21st February 2006) - Zhou, Q; Hennenberg, M; Trebicka, J; Jochem, K; Leifeld, L; Biecker, E; Sauerbruch, T; Heller, J
Abstract : Background and aims: Portal hypertension in cirrhosis is mediated in part by increased intrahepatic resistance, reflecting an increased sensitivity of the hepatic microvasculature to vasoconstrictors. Activation of the RhoA/Rho-kinase pathway is essential for contraction of vascular smooth muscle. The aim of this study was to investigate RhoA/Rho-kinase mediated regulation of the intrahepatic vascular tone in cirrhotic rats. Methods: Cirrhosis was induced by bile duct ligation (BDL). Hepatic RhoA and Rho-kinase expressions were studied by real time reverse transcription polymerase chain reaction and western blot analysis. Hepatic Rho-kinase activity in rat and human livers was assessed as phosphorylation of the Rho-kinase substrate moesin. The effect of the Rho-kinase inhibitor Y-27632 on hepatic perfusion pressure was measured in livers perfused at constant flow. The in vivo effect of intravenous application of Y-27632 was studied by haemodynamic measurements. Results: Hepatic expressions of RhoA and Rho-kinase were increased at mRNA and protein level in BDL rats. Intrahepatic moesin phosphorylation was increased in livers from cirrhotic rats and patients with alcohol induced cirrhosis. Y-27632 reduced the basal perfusion pressure of in situ perfused livers in BDL rats but not in sham operated rats. Y-27632 reduced the sensitivity to methoxamine in isolated perfused livers in sham operated rats more than in BDL rats. In vivo, Y-27632 reduced portal pressure to a greater extent in BDL rats than in sham operated rats. Intrahepatic vascular resistance was decreased in response to bolus injection of Y-27632 in BDL rats but not in sham operated rats. Conclusions: Upregulation of RhoA and Rho-kinase contributes to increased intrahepatic resistance in cirrhotic rats and to an increased sensitivity of cirrhotic livers to vasoconstrictors.